Hydrocarbon generation and expulsion modeling of different lithological combination source rocks from the Funing Formation in the Subei Basin - Peng, Jinning; Li, Longlong; Du, Chongjiao; Liu, Xu; Zhu, Jianhui; Liang, Shiyou; Qiu, Qi; Wang, Dongyan (Frontiers in Earth Science, 2023)
The oil expulsion efficiency and retention efficiency of shale affect the enrichment and preservation of shale oil. Two series of semi-closed hydrous pyrolysis experiments were performed under in situ geological conditions on a Paleogene shale sample as a comparable analog to evaluate the generation and preservation potential of shale oil in the Funing Formation shale in the Subei Basin. The results show that 1) the oil-generation capacity evolution of different lithological combination source rocks in the Funing Formation of the Subei Basin can be roughly divided into four stages: a) relatively slow oil-generating and slow gas-generating, b) relatively fast oil-generating and slow gas-generating, c) oil cracking into gas, and d) kerogen cracking into gas; 2) different lithological combinations have different hydrocarbon generation, expulsion, and retention efficiencies. The total oil generation rate and gas generation rate of pure shale are higher than those of shale with a silty interlayer, and the exchange point between the oil expulsion rate and retention rate of pure shale is earlier than that of shale with the silty interlayer, which indicates that the pure shale experienced the expulsion and retention process earlier. Oil retention mainly occurs at an EqVRo of 0.84%–1.12%, while oil is mainly discharged to the adjacent siltstone at an EqVRo of 1.12%–1.28%. Based on the simulation under geological conditions, it is recognized that for shale oil exploration in the Subei Basin, the favorable thermal maturity is at an EqVRo of 0.84%–1.12%, and the favorable lithology is the shale with the silty interlayer. On one hand, the siltstone interlayer can provide pore space for the early generated oil, and the concentration difference of hydrocarbons between the shale and the interlayer can be formed so that the generated shale can continuously enter the interlayer. On the other hand, the shale above the interlayer can be used as a cap rock to preserve shale oil. The favorable area for shale oil exploration in the Subei Basin is the area with relatively high maturity (at a VR value of about 1.1%)